Strains of dissent popular music and everyday resistance in WWII France, 1940-1945 - Jakes, Kelly (East Lansing Michigan State University Press, 2019)
Intro -- Contents -- Acknowledgments -- Preface -- Chapter 1. Repertoires of Resistance: Musical Resources for Reimagining the Nation -- Chapter 2. La France en Chantant: The Rhetorical Construction of French Identity in Songs of the Resistance Movement -- Chapter 3. Zazous in Zoot Suits: Race Play in Occupied Paris -- Chapter 4. From Prisoners to Men: Operettas on the POW Camp Stage -- Chapter 5. GI Jazz: Music and Power in Liberation France -- Conclusion -- Notes -- Bibliography -- Index
Keywords: Electronic books